2020
DOI: 10.1073/pnas.2008724117
|View full text |Cite|
|
Sign up to set email alerts
|

PIWIL1 promotes gastric cancer via a piRNA-independent mechanism

Abstract: Targeted cancer therapy aims to achieve specific elimination of cancerous but not normal cells. Recently, PIWI proteins, a subfamily of the PAZ-PIWI domain (PPD) protein family, have emerged as promising candidates for targeted cancer therapy. PPD proteins are essential for small noncoding RNA pathways. The Argonaute subfamily partners with microRNA and small interfering RNA, whereas the PIWI subfamily partners with PIWI-interacting RNA (piRNA). Both PIWI proteins and piRNA are mostly expressed in the germline… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 88 publications
1
34
0
Order By: Relevance
“…Although mRNA binding by PIWI proteins without piRNAs has been previously proposed in germ cells [13,18], this PIWI protein mode of action has not been formally demonstrated in germ cells and was not confirmed in subsequent studies [9,11,14]. piRNAs are not present in gastric cancer cells and PIWIL1 was shown to interact with mRNAs independent of piRNAs and repress them through the recruitment of nonsense-mediated mRNA decay components, promoting cancer cell proliferation, migration, and metastasis [67]. How PIWIL1 binds mRNAs without piRNAs remains to be analyzed.…”
Section: Pirna-independent Functions Of Piwi Proteinsmentioning
confidence: 96%
“…Although mRNA binding by PIWI proteins without piRNAs has been previously proposed in germ cells [13,18], this PIWI protein mode of action has not been formally demonstrated in germ cells and was not confirmed in subsequent studies [9,11,14]. piRNAs are not present in gastric cancer cells and PIWIL1 was shown to interact with mRNAs independent of piRNAs and repress them through the recruitment of nonsense-mediated mRNA decay components, promoting cancer cell proliferation, migration, and metastasis [67]. How PIWIL1 binds mRNAs without piRNAs remains to be analyzed.…”
Section: Pirna-independent Functions Of Piwi Proteinsmentioning
confidence: 96%
“…Extensive studies have uncovered an important oncogenic role for PIWIL1 in cancer tumor initiation, progression and metastasis (Liu et al, 2006(Liu et al, , 2014Siddiqi et al, 2012;Wang et al, 2012Wang et al, , 2017Zhao et al, 2012;Liang et al, 2013;Wang D.W. et al, 2014;Wang X. et al, 2014;Chen et al, 2015a;Li et al, 2015Li et al, , 2020Xie et al, 2015Xie et al, , 2018Yang et al, 2015;Cao et al, 2016;Araújo et al, 2018;Gao et al, 2018;Jiang et al, 2020;Shi et al, 2020;Zhou et al, 2020; Table 2 and Figure 4). Many studies have demonstrated that PIWIL1 drives tumorigenesis, malignant progression and metastasis by promoting cell migration, invasion, epithelial-mesenchymal transition (EMT), stem-like properties, tumorigenesis and metastasis, while inhibiting apoptosis.…”
Section: Role Of Piwil1 In Tumorigenesis and Tumor Progression And Pomentioning
confidence: 99%
“…It will be of great interest to understand whether PIWI proteins could utilize piRNAs as targeting guides to influence the stability of specific mRNA targets in tumor cells (Mai et al, 2018). However, recent observations that PIWIL1 does not associate with piRNAs in pancreatic (Li et al, 2020) and gastric cancer cells (Shi et al, 2020) supported the hypothesis that upregulated PIWIL1 protein probably functions in a piRNA-independent manner in cancer cells.…”
Section: Role Of Piwil1 In Tumorigenesis and Tumor Progression And Pomentioning
confidence: 99%
See 2 more Smart Citations